What orthopaedic surgery residents need to know about the hand and wrist? - Wadey, Veronica MR (BioMed Central, 2007)
BACKGROUND: To develop a Core Curriculum for Orthopaedic Surgery; and to conduct a national survey to assess the importance of curriculum items as judged by orthopaedic surgeons with primary affiliation non-academic. Attention for this manuscript was focused on determining the importance of topics pertaining to adult hand and wrist reconstruction. METHODS: A 281-item questionnaire was developed and consisted of three sections: 1) Validated Musculoskeletal Core Curriculum; 2) Royal College of Physician and Surgeons of Canada (RCPSC) Specialty Objectives and; 3) A procedure list. A random group of 131 [out of 156] orthopaedic surgeons completed the questionnaire. Data were analyzed descriptively and quantitatively using histograms, a Modified Hotel ling's T(2)-statistic [1] with p-value determined by a permutation test, and the Benjamini-Hochberg/Yekutieli procedure RESULTS: 131/156 (84%) orthopaedic surgeons participated in this study. 27/32 items received an average mean score of at least 3.0/4.0 by all respondents thus suggesting that 84% of the items are either "probably important" or "important" to know by the end of residency (SD range 0.007–0.228). The Benjamini-Hochberg procedure demonstrated that for 80% of the 32 × 31/2 = 496 possible pairs of hand and wrist questions did not appear to demonstrate the same distribution of ratings given that one question was different from that of another question. CONCLUSION: This study demonstrates with reliable statistical evidence, agreement on the importance of 27/32 items pertaining to hand and wrist reconstruction is included in a Core Curriculum for Orthopaedic Surgery. Residency training programs need ensure that educational opportunities focusing on the ability to perform with proficiency procedures pertaining to the hand and wrist is taught and evaluated in their respective programs.